ANALISIS STRATEGI PEMASARAN PRODUK PENGHIMPUNAN DANA DI KSPPS BMT PETA CABANG KEDIRI - Mustaqfirin, M Uzeir (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
The aim of this research is to find out the marketing strategy for fund raising products at the Kediri branch of KSPPS BMT PETA and to find out the obstacles that KSPPS BMT PETA Kediri branch often experiences in marketing fund raising products. The type of research used is field research using a qualitative descriptive approach, collecting data through observation, interviews and documentation. The results of this research are that the marketing strategy for fund raising products at KSPPS BMT PETA Kediri branch has three strategies, namely: product strategy including determining the brand and creating a motto for each savings or savings product, location strategy includes choosing an office location that feels like it is in the right place. strategic, for its promotional strategy it uses two types of promotional tools, namely advertising and publicity. However, in marketing fund-raising products there are several obstacles that are often experienced by the Kediri branch of KSPPS BMT PETA, namely: competition between BMTs in adjacent locations, lack of supplies at the Kediri branch of the KSPPS BMT PETA office, lack of human resources at the Kediri branch of the KSPPS BMT PETA office.